2003
DOI: 10.1038/sj.gt.3302131
|View full text |Cite
|
Sign up to set email alerts
|

A single administration of interleukin-4 antagonistic mutant DNA inhibits allergic airway inflammation in a mouse model of asthma

Abstract: Interleukin 4 (IL-4) is essential for the switching of B cells to IgE antibody production and for the maturation of T helper (Th) cells toward the Th2 phenotype. These mechanisms are thought to play a crucial role in the pathogenesis of the allergic airway inflammation observed in asthma. In the present study, we examined the anti-inflammatory effects of DNA administration of murine IL-4 mutant Q116D/Y119D (IL-4 double mutant, IL-4DM), which binds to the IL-4 receptor a and is an antagonist for IL-4. Immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…These IL-4-binding inhibitors act not only by inhibiting IL-4 binding to its receptor but also by preventing IL-13 from eliciting its activity, since the IL-4Ra-chain also forms a functional signaling component of the IL-13R heterodimer [16,17]. We previously reported that such plasmid administration can regulate the systemic Th immune responses in autoimmune and allergic diseases by only a single injection [14]. C3H/HeN mice, in which the development of myocarditis was induced by immunization of myosin mixed with BCG, did not develop myocarditis when they were injected with the IL-4 and IL-4SM (agonistic IL-4 mutant) DNA vaccines to inhibit the Th1-type immune response (n ¼ 10 respectively) (Fig.…”
Section: Effects Of Il-4 Il-4sm or Il-4dm Dna Administration On The mentioning
confidence: 98%
See 1 more Smart Citation
“…These IL-4-binding inhibitors act not only by inhibiting IL-4 binding to its receptor but also by preventing IL-13 from eliciting its activity, since the IL-4Ra-chain also forms a functional signaling component of the IL-13R heterodimer [16,17]. We previously reported that such plasmid administration can regulate the systemic Th immune responses in autoimmune and allergic diseases by only a single injection [14]. C3H/HeN mice, in which the development of myocarditis was induced by immunization of myosin mixed with BCG, did not develop myocarditis when they were injected with the IL-4 and IL-4SM (agonistic IL-4 mutant) DNA vaccines to inhibit the Th1-type immune response (n ¼ 10 respectively) (Fig.…”
Section: Effects Of Il-4 Il-4sm or Il-4dm Dna Administration On The mentioning
confidence: 98%
“…The plasmids encoding cDNA of antagonistic interleukin (IL)-4 double mutant (Q116D/Y119D) (IL-4DM) and agonistic IL-4 single mutant (Q116D) (IL-4SM) have been described previously [14]. The mice were intraperitoneally administered 100 mg of plasmid DNA encoding IL-4, IL-4SM or IL-4 DM on days À7, 0, 7 and 14 to regulate the Th balances.…”
Section: Administration Of Dnamentioning
confidence: 99%
“…Moreover, the amount of IL-4 in BALF from mice treated with mekabu fucoidan was lower than that of controls. IL-4 is the major factor regulating IgE production [15, 16], and IgE that is primarily associated with IL-4 induces airway inflammation. The decreased IL-4 production and OVA specific IgE levels indicate that mekabu fucoidan can improve asthma.…”
Section: Discussionmentioning
confidence: 99%
“…24 IL-4d2 represents a natural IL-4 antagonist by competing with IL-4 for binding to the nominal receptor. 25,26 Increased IL-4d2 production may not only prevent allergic reactions and subsequent airway constriction, 27 but it also appears to be associated with the control of Mtb infection, 28 presumably because of preventing a dominant Th2 response. We examined in the current report the IL-7 and IL-7R splice pattern in peripheral blood mononuclear cells (PBMCs) and in situ (lung, spleen and LNs (lymph nodes)) in a tuberculosis non-human primate (NHP) model, which allowed to study differential IL-7 and IL-7R expression profiles in response to Mtb infection.…”
Section: Introductionmentioning
confidence: 99%